Comparing apples and oranges in youth depression treatments? A quantitative critique of the evidence base and guidelines - Samuele Cortese; Glyn Lewis; Argyris Stringaris; Georgina Krebs; Marinos Kyriakopoulos; Lucy Foulkes; Carmen Moreno; Charlotte Burman; Raphaelle Delpech; Rudolph Uher; Dayna Bhudia; Despoina Miliou; et al. (BMJ Mental Health)
Objectives Should a young person receive psychotherapy or medication for their depression and on what evidence do we base this decision? In this paper, we test the factors across modalities that may influence comparability between medication and psychotherapy trials.Methods We included 92 randomised controlled trials (RCTs) of psychotherapy and medication for child and adolescent depression (mean age 4–18 years). Using meta-analyses, we compared (a) participant characteristics and (b) trial characteristics in medication and psychotherapy trials. Lastly, we examined whether psychotherapy controls are well-matched to active conditions.Results Participants in medication RCTs had higher depression severity and were more frequently male compared with psychotherapy RCTs. There was a dramatic difference in the within-subject improvement due to placebo (SMD=−1.9 (95% CI: −2.1 to −1.7)) vs. psychotherapy controls (SMD=−0.6 (95% CI: −0.9 to −0.3)). Within psychotherapy RCTs, control conditions were less intensive on average than active conditions.Conclusions Medication and psychotherapy RCTs differ on fundamental participant and methodological characteristics, thereby raising questions about their comparability. Psychotherapy controls often involve little therapist contact and are easy-to-beat comparators. These findings cast doubt on the confidence with which psychotherapy is recommended for youth depression and highlight the pressing need to improve the evidence base.